2017
DOI: 10.1007/jhep04(2017)057
|View full text |Cite
|
Sign up to set email alerts
|

Siegel modular forms and black hole entropy

Abstract: Abstract:We discuss the application of Siegel Modular Forms to Black Hole entropy counting. The role of the Igusa cusp form χ 10 in the D1D5P system is well-known, and its transformation properties are what allows precision microstate counting in this case. We apply a similar method to extract the Fourier coefficients of other Siegel modular and paramodular forms, and we show that they could serve as candidates for other types of black holes. We investigate the growth of their coefficients, identifying the dom… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(36 citation statements)
references
References 61 publications
0
36
0
Order By: Relevance
“…Are the constraints in this paper a (perhaps roundabout) way to guarantee 'slow growth' ? There has been interesting recent work studying Siegel forms obtained via multiplicative lifts and studying putative (subleading) contributions to macroscopic black hole entropy [77]. It would be educational to extend the analysis of this paper to our generating functions.…”
Section: Discussionmentioning
confidence: 97%
“…Are the constraints in this paper a (perhaps roundabout) way to guarantee 'slow growth' ? There has been interesting recent work studying Siegel forms obtained via multiplicative lifts and studying putative (subleading) contributions to macroscopic black hole entropy [77]. It would be educational to extend the analysis of this paper to our generating functions.…”
Section: Discussionmentioning
confidence: 97%
“…It is important to check if the more general twining elliptic genera considered in these references admit a 1/4 BPS dyon partition function with integral Fourier coefficients and obey the positivity constraints as expected from black hole physics. Recently multiplicative lifts of more general weak Jacobi forms 6 as well as the the Siegel modular forms of Sp(2, Z) of weight 35 and 12 were studied and were shown to have properties which make them candidates for partition of black holes [32]. It will be interesting to check if the Fourier coefficients of these Siegel modular forms also satisfy the positivity constraints required from black hole physics.…”
Section: Discussionmentioning
confidence: 99%
“…In previous work [21] we investigated the growth behavior of the Fourier coefficients of such Siegel paramodular forms for heavy states: that is, when writing the coefficients of the reciprocal of the Siegel paramodular form Φ as we define the discriminant of a state as ∆ = 4nm − l 2 . For heavy states with ∆ 1, we showed that c(m, n, l) ≈ e π √ ∆/t .…”
Section: Jhep11(2018)037mentioning
confidence: 99%